Comparison of raindrop size distribution characteristics across the Southeast Asia region - Alhilali, Manhal; Hong, Yin Lam; Din, Jafri (Universitas Ahmad Dahlan, 2018)
Satellite communication requires reliable estimates of the channel characteristics, especially with the future use of higher frequencies. Regardless of the rain rate, the shape of rain drop size distribution (DSD) start to considerably effect the specific attenuation. In this study DSDs are studied using groundbased two-dimensional video disdrometer measurements taken from Johor, Malaysia as well as two similar datasets from Gan and Manus, two equatorial islands. Integral rain parameters are studied to explain DSD variations across the southeast Asia region. Slightly higher raindrop concentrations and larger diameters were observed in Johor than in Gan or Manus, which is due to Johor being affected by not only oceanic rain- fall but land rainfall as well. The measured rainfall was classified into convective and stratiform precipitation types; the results showed that the Southeast Asia region is dominated by convective rain in terms of accumulated rainfall amount, but stratiform rain occurred more frequently. Further, seasonal variations observed in Johor were insignificant and the DSD variation was mostly due to changes in percentage occurrence of the precipitation types for each monsoon season.